Fire severity effects on ash chemical composition and water-extractable elements - Pereira, Paulo; Úbeda, Xavier; Martin, Deborah A (Geoderma, 2012)
The effects of fire in the landscape are commonly assessed through the evaluation of ash properties. Among other properties, colour is one of the methods more frequently used. However, little is known about the effect of fire severity on ash chemical and extractable elements. Ash is an important source of nutrients in terms of landscape recovery after fire. In this study we analysed the effects of fire severity (estimated using ash colour) on ash chemical properties, CaCO3, pH, Total Carbon (TC), Total Nitrogen (TN), C/N ratio and some ash water-extractable elements, such as Calcium (Ca), Magnesium (Mg), Sodium (Na), Potassium (K), Total Phosphorous (TP), Total Sulphur (TS) and Silica (Si) collected in Portugal (N=102) after three wildfires that occurred in the same ecosystem, composed mainly of maritime pine, Pinus pinaster, and cork oak, Quercus suber. The results showed significant statistical differences among ash colour at a p<0.05 for ash water-extractable K and Si, at a p<0.01 for ash water-extractable Ca, Mg, Na and TS, and the major differences were observed (at a p<0.001) for ash CaCO3, pH, TC, TN, C/N ratio and water-extractable TP. Ash CaCO3, pH and water-extractable TS increased with fire severity and ash TC, TN, C/N ratio and water-extractable TP showed a decrease. In the remaining elements, no trend is identified. Major concentrations of ash TC, TN, C/N ratio and water-extractable Ca, Mg and K were identified in very dark brown and black ash. CaCO3, pH and water-extractable TS were identified in higher quantities in light grey ash. These findings show that fire severity is an important determinant of the type and amount of water-extractable nutrients present in ash that later can be incorporated into the soil and become available for plant growth.
Keywords: Ash chemical properties; Ash colour; Ash properties; fire severity; Landscape recovery; Water-extractable elements